Case study at KSPPS BMT UGT nusantara Indonesia an analysis of using mobile applications to increase fee-based income - Muchamad Iqbal Fatah; Nur Asnawi; Segaf Segaf; Parmujianto Parmujianto (Institute of Computer Science (IOCS), 2023)
Cooperative members with businesses such as street vendors, primary food traders, and other merchants can be empowered to offer PPOB payment services owned by cooperatives. The kind of examination utilized in this study is a subjective technique. According to the findings of the research that has been conducted, a number of factors influence members to use the UGT Mobile application. These factors include the fact that it is simpler to use than mobile banking in several banks, that it is safer because it is simple to communicate and handle complaints, and that members feel ownership because they are also cooperative owners. Based on the result, BMT UGT individuals are not exactly ideal in utilizing the Mobile UGT application because of the absence of information about the UGT Portable application. Then, BMT UGT's fee-based income growth is below par as a result of Mobile UGT's lack of maximum exposure to BMT UGT members and an uneven distribution of employee knowledge regarding the application's benefits. Thus, this study provides valuable insights into the use of mobile applications to increase fee-based income in microfinance institutions.